High-specific-energy relay type composite positive electrode material for thermal battery, preparation method of high-specific-energy relay type composite positive electrode material and prepared thermal battery

By using relay composite cathode materials of transition metal chloride and transition metal disulfide in thermal batteries, the problem of poor thermal stability of existing cathode materials at high temperatures is solved, and the effect of high specific energy and long discharge time is achieved.

CN119560525AInactive Publication Date: 2025-03-04CHINA ELECTRONIC TECH GRP CORP NO 18 RES INST
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411652934.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing thermal battery positive electrode materials have poor thermal stability at high temperatures, resulting in poor discharge performance and cannot meet the high specific energy needs of new weapons and equipment.

Method used

The relay composite cathode material of transition metal chloride and transition metal disulfide is used to improve the cathode discharge voltage and specific energy by mixing different proportions of transition metal chloride and disulfide materials.

Benefits of technology

It effectively improves the maximum voltage and specific energy of the thermal battery, extends the discharge time, and enhances the heat resistance of the positive electrode material. It is suitable for thermal battery applications with high specific energy at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560525A_ABST
    Figure CN119560525A_ABST
Patent Text Reader

Abstract

Transition metal chloride has the advantages of being good in thermal stability, high in discharge voltage, high in theoretical specific capacity and the like, but the conductivity of the transition metal chloride is poor, and the difference between the actual discharge performance and the theoretical value is large. Therefore, the material is difficult to apply on a large scale in thermal batteries. As a common thermal battery positive electrode material, the transition metal disulfide has good conductivity and long working time, and the development of the transition metal disulfide is limited by lower decomposition temperature and specific energy. The composite positive electrode material prepared from the transition metal chloride and the transition metal disulfide has relatively high thermal stability, and the specific energy of the positive electrode of the thermal battery can be effectively improved by utilizing the high voltage of the chloride in the early stage and a relatively long and stable voltage platform of the disulfide to form a relay reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal batteries, and in particular relates to a high-energy-density relay composite positive electrode material for a thermal battery, a preparation method thereof, and a thermal battery prepared therefrom. Background Art

[0002] Thermal batteries, also known as heat-activated reserve batteries, are chemical reserve power sources. They are primary batteries that use the battery's own heating system to heat non-conductive solid salt electrolytes at room temperature to a molten ion state to work. Due to its many advantages such as short activation time, high power density, long storage time, and wide ambient temperature range, it is widely used in aerospace, torpedoes, missiles and other systems, and occupies an important position in the military field.

[0003] As a power source for national defense equipment, the technological development of thermal batteries will directly affect the combat performance of weapon systems. In order to adapt to the electrical energy needs of weapon systems with different strike purposes in modern warfare, the specific energy requirements of thermal batteries are getting higher and higher. The operating temperature of thermal batteries is above 500°C or even higher, which places high demands on the thermal stability of positive electrode materials. At present, the commonly used positive electrode materials for thermal batteries are transition metal sulfides, which will decompose at about 580°C, resulting in low positive electrode utilization, which seriously restricts the discharge performance of thermal batteries and has gradually been unable to meet the needs of new weapons and equipment. Therefore, developing a composite positive electrode material with high heat resistance and high specific energy to replace the traditional sulfide positive electrode and improve the utilization efficiency of positive electrode materials is an important direction for the current development of thermal batteries.

[0004] Transition metal disulfide is a widely used positive electrode material for thermal batteries. It has the advantages of good compatibility with molten salt electrolytes and stable discharge performance, but its thermal stability is poor and the voltage platform is low. Transition metal chloride positive electrode materials have the advantages of good thermal stability, high discharge platform, and high specific capacity, which meet the needs of high-voltage and high-power thermal batteries. However, its poor conductivity, long activation time, easy melting and leaching with the electrolyte during discharge, resulting in battery short circuit, and a large gap between the actual discharge capacity and the theoretical value limit the application of this material in thermal batteries. Taking advantage of the high voltage platform of transition metal chloride positive electrode materials and the stable discharge performance of transition metal disulfide positive electrode materials, the positive electrode discharge voltage is increased through the relay reaction of composite positive electrode materials, thereby increasing the specific energy of the material. Summary of the invention

[0005] In view of this, the present invention provides a high specific energy relay composite positive electrode material for thermal batteries and a preparation method and application thereof. The high specific energy relay composite positive electrode material for thermal batteries has the characteristics of high voltage, discharge platform relay, long discharge time and high specific energy; the preparation method is simple, the raw materials are abundant, the environment is friendly, and it is suitable for promotion and use.

[0006] The specific technical scheme adopted by the present invention is: a high specific energy relay composite positive electrode material for a thermal battery, comprising a transition metal chloride positive electrode material and a transition metal disulfide positive electrode material, wherein the mass ratio of the transition metal chloride positive electrode material to the transition metal disulfide positive electrode material is 5:95 to 90:10;

[0007] The positive electrode material of the transition metal chloride is prepared in the following steps:

[0008] (1) placing the transition metal chloride raw material powder under inert gas protection, heating at a constant temperature of 100° C. to 900° C. for 4 h to 48 h, and then pre-calcining and drying to obtain anhydrous compound powder①;

[0009] (2) adding the carbon coating agent to powder ① in proportion and mixing evenly, heating the mixture at a constant temperature of 100° C. to 900° C. in an inert atmosphere for 2 h to 48 h, and cooling the mixture to obtain powder ②;

[0010] (3) taking out the powder ②, crushing and sieving, and obtaining a transition metal chloride positive electrode material;

[0011] The preparation steps of the transition metal disulfide positive electrode material are as follows: the transition metal disulfide and the additive are weighed in proportion and mixed evenly, placed in an inert atmosphere for high temperature sintering at 300° C. to 700° C. for 2 h to 48 h, and after cooling, crushed and sieved to form the transition metal disulfide positive electrode material;

[0012] The additive is a lithium agent Li 2 O and eutectic salt electrolyte, transition metal disulfide accounts for 70% to 85% by mass, and the lithium agent Li 2 The mass percentage of O is 0.3% to 4%, and the mass percentage of eutectic salt electrolyte is 13% to 28%.

[0013] The carbon coating agent is one or more of citric acid, asphalt, glucose, sucrose, graphene, and carbon nanotubes; the mass percentage of the carbon coating agent is 1% to 20%; and the sieve specification is 80 to 300 meshes.

[0014] The eutectic salt electrolyte is one of LiCl-KCl, LF-LiCl-LiBr, LiF-LiBr-KBr and LiCl-LiBr-KBr.

[0015] The sieve mesh specification is 80 to 300 meshes.

[0016] The transition metal chloride is FeCl 2 、CoCl 2 、NiCl 2 、PbCl 2 , KNiCl 3、LiMnCl 4 , Li 6 VCl 8 One or more of.

[0017] The transition metal disulfide is MS 2 , M=Fe, Co, Ni,, Mn, Mo, W.

[0018] The transition metal disulfide is FeS 2 、CoS 2 、NiS 2 , Fe x Ni 1-x S 2 (0<x<1), Fe x Co 1-x S 2 (0<x<1), Co x Ni 1-x S 2 (0<x<1), Fe x Co y Ni 1-x-y S 2 (0<x+y<1), MoS 2 , WS 2 One or more of .

[0019] The positive electrode material of the transition metal chloride is a block particle with a particle size of 10 to 150 μm, and the positive electrode material of the transition metal disulfide is a block particle with a particle size of 20 to 200 μm.

[0020] The preparation method of the high specific energy relay composite positive electrode material for the above-mentioned thermal battery is to mix the positive electrode material of transition metal chloride and the positive electrode material of transition metal disulfide uniformly according to the mass ratio, mechanically stir or ball mill, and the mixing time is 5min to 120min to obtain the relay composite positive electrode material.

[0021] A thermal battery comprises the above-mentioned high-energy-density relay composite positive electrode material for thermal batteries or the high-energy-density relay composite positive electrode material for thermal batteries obtained by the above-mentioned preparation method.

[0022] Beneficial effects of the present invention: The composite positive electrode material prepared by using transition metal chloride positive electrode material and transition metal disulfide positive electrode material can effectively utilize the advantages of chloride high voltage platform and disulfide stable discharge, and through relay reaction, improve the positive electrode discharge voltage and thus improve the specific energy of the material. In addition, due to the excellent heat resistance of chloride itself, it can also effectively resist the large heat shock on the surface of the thermal battery positive electrode material, thereby comprehensively improving the electrochemical performance of the thermal battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is the thermal battery discharge curve of the high specific energy relay composite positive electrode material prepared in Example 1 of the present invention and the positive electrode material prepared in Comparative Example 1.

[0024] Figure 2 These are the thermal battery discharge curves of the high specific energy relay composite positive electrode material prepared in Example 2 of the present invention and the positive electrode material prepared in Comparative Example 2. DETAILED DESCRIPTION

[0025] In order to better understand the present invention, the technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only exemplary illustrations and explanations of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect. In addition, the endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, between the endpoint values ​​of each range, between the endpoint values ​​of each range and a separate point value, and between separate point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered as specifically disclosed in this article.

[0026] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0027] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.

[0028] The invention discloses a high-energy-density relay composite positive electrode material for a thermal battery. The composite positive electrode material comprises a transition metal chloride positive electrode material and a transition metal disulfide positive electrode material.

[0029] Preferably, the transition metal chloride is FeCl 2 、CoCl 2 、NiCl 2 、PbCl 2 , KNiCl 3 、LiMnCl 4 , Li 6 VCl 8 The transition metal disulfide is MS 2 , M=Fe, Co, Ni, , Mn, Mo, W. The transition metal disulfide is FeS 2 、CoS 2 、NiS 2 , Fe x Ni 1-xS 2 (0<x<1), Fe x Co 1-x S 2 (0<x<1), Co x Ni 1-x S 2 (0<x<1), Fe x Co y Ni 1-x-y S 2 (0<x+y<1), MoS 2 , WS 2 One or more of .

[0030] Preferably, the transition metal chloride positive electrode material is block particles with a particle size of 10 to 150 μm.

[0031] Preferably, the transition metal disulfide positive electrode material is a block particle with a particle size of 20 to 200 μm.

[0032] According to an embodiment of the present invention, the composite positive electrode material is formed by mixing a transition metal chloride positive electrode material and a transition metal disulfide positive electrode material in a certain proportion, and has a mixed multiphase structure.

[0033] The present invention provides a method for preparing a high specific energy relay composite positive electrode material for a thermal battery, and the specific steps are as follows:

[0034] Preparation of transition metal chloride cathode materials, including:

[0035] (1) placing the transition metal chloride raw material powder under inert gas protection, heating at a constant temperature of 100° C. to 900° C. for 4 h to 48 h, and then pre-calcining and drying to obtain anhydrous compound powder①;

[0036] (2) adding the carbon coating agent to powder ① in proportion and mixing them evenly, heating them at a constant temperature of 100° C. to 900° C. in an inert atmosphere for 2 h to 48 h, and obtaining powder ② after cooling;

[0037] (3) Take out the powder ②, crush and sieve it to obtain transition metal chloride positive electrode material A.

[0038] Preferably, the carbon coating agent is one or more of citric acid, asphalt, glucose, sucrose, graphene, and carbon nanotubes;

[0039] Preferably, the mass percentage of the carbon coating agent is 1wt.% to 20wt.%;

[0040] Preferably, the mesh size is 80 to 300 meshes.

[0041] Preparation of transition metal disulfide cathode materials, including:

[0042] The transition metal disulfide and the additive are weighed in proportion and mixed evenly, placed in an inert atmosphere for high-temperature sintering at 300°C to 700°C for 2h to 48h, and then crushed and sieved to form a transition metal disulfide positive electrode material B after cooling.

[0043] Preferably, the mesh size is 80-300 meshes;

[0044] Preferably, the additive is a lithium-ionizing agent Li2O and a eutectic salt electrolyte;

[0045] The mass percentage of transition metal disulfide is 70% to 85%, the mass percentage of lithium agent Li2O is 0.3% to 4%, and the mass percentage of eutectic salt electrolyte is 13% to 28%;

[0046] Preferably, the eutectic salt electrolyte is one of LiCl-KCl, LF-LiCl-LiBr, LiF-LiBr-KBr and LiCl-LiBr-KBr.

[0047] Relay type composite cathode material preparation, including:

[0048] The positive electrode material of transition metal chloride and the positive electrode material of transition metal disulfide are uniformly mixed in a certain mass ratio to obtain a relay type composite positive electrode material.

[0049] Preferably, the mass ratio of the positive electrode material of the transition metal chloride to the positive electrode material of the transition metal disulfide is 5:95 to 90:10;

[0050] Preferably, the mixing method is one of mechanical stirring and ball milling, and the mixing time is 5 min to 120 min.

[0051] The present invention also provides a thermal battery, which comprises the above-mentioned positive electrode material. Preferably, the thermal battery is a lithium-based thermal battery.

[0052] In the following embodiments of the present invention: Thermal battery prototype electrical performance test method: at 2T / cm 2 The composite positive electrode material powder (the final product prepared in Examples 1-4 and Comparative Examples 1-3) and the ternary all-lithium salt electrolyte powder (LiF-LiCl-LiBr) were pressed into single-layer sheets under a pressure of , and stacked in the order of positive electrode sheet, electrolyte sheet, negative electrode, and current collector sheet to form a single cell. 15 groups of single cells were connected in series and then pressurized and tightened, and then sealed into a battery housing to assemble a reserve lithium battery prototype. The assembled hot battery prototype was subjected to a discharge test under 8A constant current and load conditions.

[0053] Example 1

[0054] S1: Preparation of transition metal chloride cathode materials

[0055] First, weigh a certain amount of NiCl 2 The material was placed in an atmosphere protection furnace with Ar protection, and pre-calcined at a constant temperature of 700°C for 12 hours to obtain anhydrous compound powder. Citric acid was weighed according to a mass fraction of 5wt% and mechanically mixed with the powder for 10min, placed in an atmosphere protection furnace with Ar protection, and calcined at a constant temperature of 600°C for 6 hours. After cooling, it was crushed through a 200-mesh sieve to obtain a positive electrode material of transition metal chloride.

[0056] S2: Preparation of cathode materials of transition metal disulfides

[0057] FeS 2 With Li 2 The O lithium agent and the LiF-LiCl-LiBr eutectic salt electrolyte were mechanically mixed at a mass ratio of 80:2:18 for 10 minutes, and then kept at a constant temperature of 400°C for 4 hours in a high-temperature atmosphere furnace filled with argon. After the constant temperature was completed, the material was taken out from the high-temperature atmosphere furnace, crushed and passed through a 100-mesh sieve to obtain a positive electrode material of transition metal disulfide.

[0058] S3: Relay composite cathode material preparation

[0059] The transition metal chloride positive electrode material and the transition metal disulfide positive electrode material were weighed at a mass ratio of 30:70, and ball-milled for 60 minutes at a rotation speed of 300 rpm to obtain a relay-type composite positive electrode material.

[0060] The discharge test results show that the maximum voltage of the thermal battery prototype assembled with relay-type composite positive electrode materials is increased by 18% and the specific energy is increased by 7%.

[0061] Example 2

[0062] S1: Preparation of transition metal chloride cathode materials

[0063] First, weigh a certain amount of NiCl 2 The material was placed in an atmosphere protection furnace with Ar protection, and pre-calcined at a constant temperature of 700°C for 12 hours to obtain anhydrous compound powder. Citric acid was weighed according to a mass fraction of 5wt% and mechanically mixed with the powder for 10min, placed in an atmosphere protection furnace with Ar protection, and calcined at a constant temperature of 600°C for 6 hours. After cooling, it was crushed through a 200-mesh sieve to obtain a positive electrode material of transition metal chloride.

[0064] S2: Preparation of cathode materials of transition metal disulfides

[0065] CoS 2 With Li 2O lithium agent, LiF-LiCl-LiBr eutectic salt electrolyte according to the mass ratio of 75:1:24 weighed, ball milled at a speed of 300 rpm, mixed for 30 minutes, and then kept constant temperature in a high temperature atmosphere furnace filled with argon, the constant temperature is 500 ° C, the constant temperature time is 2 hours. After the constant temperature is completed, the broken pieces are taken out from the high temperature atmosphere furnace and passed through a 120 mesh sieve to obtain the positive electrode material of transition metal disulfide.

[0066] S3: Relay composite cathode material preparation

[0067] The positive electrode material of transition metal chloride and the positive electrode material of transition metal disulfide were weighed at a mass ratio of 20:80, and ball-milled for 60 minutes at a rotation speed of 200 rpm to obtain a relay-type composite positive electrode material.

[0068] The discharge test results show that the maximum voltage of the thermal battery prototype assembled using relay-type composite positive electrode materials is increased by 20% and the specific energy is increased by 10%.

[0069] Example 3

[0070] S1: Preparation of transition metal chloride cathode materials

[0071] First, weigh a certain amount of LiMnCl 4 The material was placed in an atmosphere protection furnace with Ar protection, and pre-calcined at a constant temperature of 600°C for 15 hours to obtain anhydrous compound powder. Sucrose was weighed according to a mass fraction of 12wt% and mechanically mixed with the powder for 15min, placed in an atmosphere protection furnace with Ar protection, and calcined at a constant temperature of 600°C for 8 hours. After cooling, it was crushed through a 200-mesh sieve to obtain a positive electrode material of transition metal chloride.

[0072] S2: Preparation of cathode materials of transition metal disulfides

[0073] FeS 2 With Li 2 O lithium agent, LiF-LiCl-LiBr eutectic salt electrolyte are mechanically mixed at a mass ratio of 80:2:18 for 10 minutes, and then kept constant temperature in a high temperature atmosphere furnace filled with argon, the constant temperature is 400 ° C, and the constant temperature time is 4 hours. After the constant temperature is completed, the material is taken out from the high temperature atmosphere furnace, crushed and passed through a 100 mesh sieve to obtain a transition metal disulfide positive electrode material.

[0074] S3: Relay composite cathode material preparation

[0075] The positive electrode material of transition metal chloride and the positive electrode material of transition metal disulfide were weighed at a mass ratio of 30:70, and ball-milled for 60 minutes at a rotation speed of 300 rpm to obtain a relay-type composite positive electrode material.

[0076] The discharge test results show that the maximum voltage of the thermal battery prototype assembled using relay-type composite positive electrode materials is increased by 15% and the specific energy is increased by 6%.

[0077] Example 4

[0078] S1: Preparation of transition metal chloride cathode materials

[0079] First, weigh a certain amount of KNiCl 3 The material is placed in an atmosphere protection furnace filled with Ar protection, and pre-calcined at a constant temperature of 700°C for 10 hours to obtain anhydrous compound powder. Carbon nanotubes weighed at a mass fraction of 3wt% are mixed with the powder by ball milling for 120min at a speed of 300 rpm, and then placed in an atmosphere protection furnace filled with Ar protection, calcined at a constant temperature of 600°C for 10 hours, and crushed through a 200-mesh sieve after cooling to obtain a positive electrode material of transition metal chloride.

[0080] S2: Preparation of cathode materials of transition metal disulfides

[0081] NiS 2 With Li 2 O lithium agent, LiF-LiCl-LiBr eutectic salt electrolyte according to the mass ratio of 78:2:20 weighed, ball mill speed 300 rpm, mixed for 30min, and then in a high temperature atmosphere furnace filled with argon gas constant temperature, constant temperature of 400 ° C, constant temperature time for 2 hours. After the constant temperature is completed, the broken out from the high temperature atmosphere furnace and passed through a 120 mesh sieve to obtain the positive electrode material of transition metal disulfide.

[0082] S3: Relay composite cathode material preparation

[0083] The transition metal chloride positive electrode material and the transition metal disulfide positive electrode material were weighed at a mass ratio of 20:80, and ball-milled at a rotation speed of 200 rpm for 60 min to obtain a relay-type composite positive electrode material.

[0084] The discharge test results show that the maximum voltage of the thermal battery prototype assembled with relay-type composite positive electrode materials is increased by 12% and the specific energy is increased by 5%.

[0085] Comparative Example 1

[0086] FeS 2 With Li 2 O lithium agent, LiF-LiCl-LiBr eutectic salt electrolyte are mechanically mixed at a mass ratio of 80:2:18 for 10 minutes, and then kept constant temperature in a high temperature atmosphere furnace filled with argon, the constant temperature is 400 ° C, and the constant temperature time is 4 hours. After the constant temperature is completed, the material is taken out from the high temperature atmosphere furnace, crushed and passed through a 100 mesh sieve to obtain a transition metal disulfide positive electrode material.

[0087] Comparative Example 2

[0088] CoS 2 With Li 2 O lithium agent, LiF-LiCl-LiBr eutectic salt electrolyte according to the mass ratio of 75:1:24 weighed, ball milled at a speed of 300 rpm, mixed for 30 minutes, and then kept constant temperature in a high temperature atmosphere furnace filled with argon, the constant temperature is 500 ° C, the constant temperature time is 2 hours. After the constant temperature is completed, the material is taken out from the high temperature atmosphere furnace and crushed and passed through a 120 mesh sieve to obtain a transition metal disulfide positive electrode material.

[0089] Comparative Example 3

[0090] NiS 2 With Li 2 O lithium agent, LiF-LiCl-LiBr eutectic salt electrolyte according to the mass ratio of 78:2:20 weighed, ball mill speed 300 rpm, mixed for 30min, and then in a high temperature atmosphere furnace filled with argon gas constant temperature, constant temperature of 400 ° C, constant temperature time for 2 hours. After the constant temperature is completed, the high temperature atmosphere furnace is taken out of the crushed and passed through a 120 mesh sieve to obtain a transition metal disulfide positive electrode material.

[0091] from Figure 1 It can be seen that FeS 2 The highest voltage of the positive electrode material in the thermal battery prototype (mass 582g) is 32.3V, the working time is 378s when the discharge cut-off voltage is 25V, and the specific energy is 42.58Wh / kg. The highest voltage of the composite positive electrode material in the thermal battery prototype (581g) is 38.12V, the working time is 392s when the discharge cut-off voltage is 25V, and the specific energy is 45.57Wh / kg. The discharge test results show that the maximum voltage of the thermal battery prototype assembled with the relay composite positive electrode material is increased by 18% and the specific energy is increased by 7%.

[0092] from Figure 2 It can be seen that CoS 2 The highest voltage of the positive electrode material in the thermal battery prototype (mass 579g) is 30.05V, the working time is 362s when the discharge cut-off voltage is 25V, and the specific energy is 40.85Wh / kg. The highest voltage of the composite positive electrode material in the thermal battery prototype (579g) is 36.06V, the working time is 388s when the discharge cut-off voltage is 25V, and the specific energy is 44.94Wh / kg. The discharge test results show that the maximum voltage of the thermal battery prototype assembled with the relay composite positive electrode material is increased by 20% and the specific energy is increased by 10%.

[0093] The embodiments described above are only used to illustrate the technical ideas and features of the present invention, and their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. The patent scope of the present invention cannot be limited only by these embodiments. That is, any equivalent changes or modifications made to the spirit disclosed by the present invention still fall within the patent scope of the present invention.

Claims

1. A high specific energy relay composite positive electrode material for a thermal battery, characterized in that: A positive electrode material comprising a transition metal chloride and a positive electrode material comprising a transition metal disulfide, wherein the mass ratio of the positive electrode material of the transition metal chloride to the positive electrode material of the transition metal disulfide is 5:95 to 90:10; The positive electrode material of the transition metal chloride is prepared in the following steps: (1) placing the transition metal chloride raw material powder under inert gas protection, heating at a constant temperature of 100° C. to 900° C. for 4 h to 48 h, and then pre-calcining and drying to obtain anhydrous compound powder①; (2) adding the carbon coating agent to powder ① in proportion and mixing them evenly, heating them at a constant temperature of 100° C. to 900° C. in an inert atmosphere for 2 h to 48 h, and obtaining powder ② after cooling; (3) taking out the powder ②, crushing and sieving, and obtaining a transition metal chloride positive electrode material; The preparation steps of the transition metal disulfide positive electrode material are as follows: the transition metal disulfide and the additive are weighed in proportion and mixed evenly, placed in an inert atmosphere for high temperature sintering at 300° C. to 700° C. for 2 h to 48 h, and after cooling, crushed and sieved to form the transition metal disulfide positive electrode material; The additives are a lithiumation agent Li2O and a eutectic salt electrolyte, wherein the mass percentage of the transition metal disulfide is 70% to 85%, the mass percentage of the lithiumation agent Li2O is 0.3% to 4%, and the mass percentage of the eutectic salt electrolyte is 13% to 28%.

2. The high specific energy relay composite positive electrode material for thermal battery according to claim 1, characterized in that: The carbon coating agent is one or more of citric acid, asphalt, glucose, sucrose, graphene, and carbon nanotubes; the mass percentage of the carbon coating agent is 1% to 20%; and the sieve specification is 80 to 300 meshes.

3. The high specific energy relay composite positive electrode material for thermal battery according to claim 1, characterized in that: The eutectic salt electrolyte is one of LiCl-KCl, LF-LiCl-LiBr, LiF-LiBr-KBr and LiCl-LiBr-KBr.

4. The high specific energy relay composite positive electrode material for thermal battery according to claim 1, characterized in that: The sieve mesh specification is 80 to 300 meshes.

5. The high specific energy relay composite positive electrode material for thermal battery according to claim 1, characterized in that: The transition metal chloride is one or more of FeCl2, CoCl2, NiCl2, PbCl2, KNiCl3, LiMnCl4, and Li6VCl8.

6. The high specific energy relay composite positive electrode material for thermal battery according to claim 1, characterized in that: The transition metal disulfide is MS2, where M=Fe, Co, Ni, Mn, Mo, W.

7. The high specific energy relay composite positive electrode material for thermal battery according to claim 1, characterized in that: The transition metal disulfide is FeS2, CoS2, NiS2, Fe x Ni 1-x S2(0<x<1),Fe x Co 1-x S2(0<x<1),Co x Ni 1-x S2(0<x<1),Fe x Co y Ni 1-x-y One or more of S2(0<x+y<1), MoS2, WS2.

8. The high specific energy relay composite positive electrode material for thermal battery according to claim 1, characterized in that: The positive electrode material of the transition metal chloride is a block particle with a particle size of 10 to 150 μm, and the positive electrode material of the transition metal disulfide is a block particle with a particle size of 20 to 200 μm.

9. The method for preparing a high specific energy relay composite positive electrode material for a thermal battery according to any one of claims 1 to 8, characterized in that: The positive electrode material of transition metal chloride and the positive electrode material of transition metal disulfide are uniformly mixed according to mass ratio, mechanically stirred or ball milled, and the mixing time is 5 minutes to 120 minutes to obtain a relay type composite positive electrode material.

10. A thermal battery, characterized in that: The invention comprises the high specific energy relay type composite positive electrode material for a thermal battery as described in any one of claims 1 to 8 or the high specific energy relay type composite positive electrode material for a thermal battery obtained by the preparation method as described in claim 9.

Citation Information

Patent Citations

  • Preparation method of thermal battery positive electrode material, and thermal battery made of thermal battery positive electrode material

    CN106207085A

  • Ternary composite positive electrode material for thermal battery and preparation method thereof

    CN110783540A

  • Cathodal pellet for thermal battery, method for fablicatign the same, and thermal battery having the same

    KR1020100088492A